Estimation of Whole Blood (WB) using Unscented Kalman Filter in Surabaya. Issue 1 (June 2020) - Muhith, Abdul; Herlambang, Teguh; Haris, Abdul; Rahmalia, Dinita
Abstract: As the need for blood transfusion increases, an improved blood stock management for blood transfusion is required. In terms of quality and quantity, blood transfusion is needed by patients with various health problems. Because of that need, it is urgent that the stability of blood stock be maintained to avoid possible excessive blood stock that leads to unnecessary blood disposal. For that purpose, prediction of blood demand is required. One of the blood transfusion units is PMI, a national organization dealing with social concern and humanity field. The objective of this paper is to make estimation of blood demand for PRC and WB at PMI Surabaya using UKF method. The simulation results show that the UKF method is effective with a high accuracy and an error of less than 4%.